POLITICAL ECONOMY OF RELIGIOUS AND CULTURAL SYMBOLS IN THE SOAP OPERA OF TUKANG BUBUR NAIK HAJI AT RCTI - Yasir, Yasir (Al-Ulum, 2015)
Television is a very influential media and important tool in capital accumulation. This study aims to reveal the use of Islamic and Betawi ethnic symbols, workers, and also the audiences of Tukang Bubur Naik Haji (TBNH) soap opera at RCTI. This research used a political economy of communication perspective. The data were collected by using interview, observation, documentation, and literature study. The result shows that the religious symbols of Islam and Betawi culture have been exploited as comodity to be traded. Those symbols have been commercialized dan manipulated through the use of sensational, provocative, and hyperbole words or sentences to entertain audiences and to attract the advertisers. The hyper-comercialization and politicization of symbols caused the soap opera workers and Moslem audiences have been exploited.Â -----Televisi adalah media yang sangat berpengaruh dan juga alat yang penting dalam mengakumulasi modal. Tulisan ini bertujuan untuk mengungkap pemanfaatan simbol agama Islam dan budaya Betawi, pekerja sinetron dan khalayak sinetron Tukang Bubur Naik Haji (TBNH) di RCTI. Penelitian ini menggunakan pendekatan ekonomi politik komunikasi. Untuk mengumpulkan data peneliti melakukan wawancara mendalam, observasi, dokumentasi dan studi literatur. Hasil penelitian menunjukkan bahwa simbol agama dan budaya Betawi dieksploitasi sebagai komoditas untuk diperjualbelikan. Simbol tersebut dikomersialisasi dan diselewengkan melalui penggunaan kata-kata dan kalimat serta tayangan yang sensasional, provokatif dan hiperbola untuk menghibur dan menarik khalayak. Hiper-komersialisasi dan politisasi simbol ini menyebabkan pekerja sinetron dan khalayak muslim ikut dikomodifikasi dan dieksploitasi.